SOSIALISASI SISTEM DIGITAL PENDAFTARAN SEMINAR PROPOSAL, HASIL PENELITIAN, DAN UJIAN SARJANA BERBASIS DATABASE - Barus, Carolina Sri Athena; Asep, Asep; Helmi, Dewilna (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2023)
The tri dharma of higher education consist of teaching, research, and community service elements that must be carried out by faculty members in higher education institutions. Community service provides a platform for faculty members to contribute to society according to their respective areas of expertise. Learning is an activity carried out to achieve the goals of education. One form of the learning process in higher education is the completion of a final project. The community service provided in this case takes the form of a digital-based service, namely a database that provides convenience for students in completing their final project administration services. The community service method used in this case consists of lectures and discussions to socialize the digital system that can be used by students to facilitate the completion of final project administration tasks. Through this activity, data is collected descriptively by describing responses and feedback. The socialization activity carried out in community service has a good response rate with an achievement percentage of 82.33%, thus it can be seen as an alternative to increasing motivation in developing IT knowledge.